Hindu values based management in transportation service companies - Diana, I Wayan; Gelgel, I Putu; Wimba, I Gusti Ayu (International research journal of management, IT and social sciences, 2020)
Business sustainability is the hope of business-people in facing the economic crisis and a very dynamic situation in the era of revolution 4.0. Transportation Service Company is owned by Hindu entrepreneur PT. Puspa Jaya Transport, Lampung Province, is a family company that managed to get through difficult times, the multidimensional crisis of 1997/1998 until the second generation still exists and dominates transportation services in Lampung. The data was collected employing observation, interview, and document study techniques. The data is processed in interpretive descriptions through three stages, data reduction, data presentation, and concluding. The results showed to develop company employees to become hard workers, honest and with high integrity, it is necessary to instill values that can encourage achievement from within itself. These values are found in life goals, namely: Catur Purusha Artha. Of course, it is based on honesty, as revealed in the Rgweda Scripture: Yes, Hyang Widhi, I hope you will bestow divine wealth, encourage us to acquire wealth in the form of glory, may our prosperity be based on honest efforts.